Effects of “Reed A Dream” Insecticide on Selected Biomarkers of Kidney, Liver, and Lipid Profile in Wistar Rats: Subject: Biotechnology - Joshua, David; Peters , Dikioye Emmanue; Ikewuchi, Jude Chigozie (BioScientific Review, 2022)
This study investigated the effects of “Reed A Dream” (RD) insecticide on selected biomarkers of kidney, liver, and lipid profile in Wistar rats. Twenty-five (25) rats of both sexes (weighing 50-114 g) were divided into 5 groups, comprising of control (0.5mL water), N-hexane only (0.5mL), RD(50% vol/vol) + N-hexane, RD(25% vol/vol) + N-hexane, and RD (12.5% vol/vol) + N-hexane, also labelled as groups 1-5 respectively. After 2 weeks of oral daily administration, the animals were sacrificed; blood, liver, kidney, and heart tissues were taken for biochemical and histopathological investigations. A non-significant decreased (p≥0.05) in plasma concentration of total protein, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) in groups 3-5, a significant decrease (p≤0.05) in albumin (groups 3-5); a non-significant increased in creatinine, gamma glutamyltranspeptidase (GGT) in groups 3-4 was observed, as compared with the control group; Moreover, a significant increased (p≤ 0.05) in urea in groups 3-5 when compared with the control group. Histology of the liver tissue (Group 3) revealed a central vein with mild congestion, while kidney tissues (groups 3-5) showed visible congestion of glomerulus, and heart tissue (group 3-5) showed interstitial deposition of collagens, as compared with the control group. RD insecticide caused acute nephrotoxicity and mild hepatotoxicity in Wistar rats on oral exposure.